Book review: water management in Islam - Ali Shah, Syed Alamdar; Sukmana, Raditya; Fianto, Bayu Arie (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this manuscript is to present a book review of “Water Management in Islam” published by United Nations University Press, International Development Research Centre. The Book was published in the year 2001 when shariah compliance perspective was in its infancy. However, with the rapid growth of shariah compliance in almost every sector of the economy it is very important to review the recommendations of leading scholars in the area of water management as well. The book is the product of findings from a workshop on water management in Islamic world held in Jordan 1998 with the focus to contribute in local and international policies that improve quality and accessibility of water in MENA region. The contributions are towards water demand management, fair water reuse and fair pricing of water. Most valuable contribution of the book is reconciliation between Dublin principles and Islamic principles.